Arabic Language Education Student’s Perceptions of The School Field Experience Program II in 2025 - Yuli Novita Ratnawati; Mukhshon Nawawi; Raswan (Penerbit Minhaj Pustaka, 2026)
مستخلص البحث يواجه تنفيذ برنامج التعرّف على البيئة المدرسية (PLP) II لدى طلاب قسم تعليم اللغة العربية عددًا من التحدّيات، من أبرزها الفجوة بين النظرية والتطبيق، وضعف الجاهزية النفسية، وتعقيد تعليم اللغة العربية داخل الصف، مما يؤثّر في إدراك الطلاب تجاه البرنامج. وتهدف هذه الدراسة إلى التعرّف على إدراك طلاب قسم تعليم اللغة العربية تجاه تنفيذ برنامج PLP II لعام 2025 من الجوانب المعرفي والوجداني والنزوعي، إضافة إلى تحديد العوامل المؤثّرة في هذه الإدراك. اعتمدت الدراسة المنهج الوصفي بالمدخل الكمي، وتمّ جمع البيانات باستخدام الاستبانة. وبلغت عيّنة الدراسة 72 طالبًا تم اختيارهم بطريقة العيّنة العشوائية البسيطة. أمّا تحليل البيانات فتم باستخدام التحليل الإحصائي الوصفي وتحليل العوامل الاستكشافي (EFA). وأظهرت النتائج أنّ إدراك الطلاب تجاه تنفيذ برنامج PLP II يقع في فئة إيجابية. فقد بلغ متوسّط الجانب المعرفي 13،89 (إيجابي)، والجانب الوجداني 14،14 (إيجابي)، والجانب النزوعي 9،99 (إيجابي). كما كشفت نتائج تحليل العوامل عن ثلاثة عوامل رئيسة مؤثّرة، وهي: دعم البيئة التعليمية ودافعية التعلّم، والإرشاد والإعداد الأكاديمي، والخبرة والتأمّل الذاتي. وتؤكّد هذه النتائج أنّ إدراك الطلاب يتشكّل من خلال التفاعل بين الفهم النظري، والخبرة الميدانية، والدعم التربوي خلال تنفيذ برنامج PLP II. ABSTRACT The implementation of the School Field Experience (PLP) II program for Arabic Language Education students is still characterised by a gap between theory and practice and a lack of psychological readiness. which contribute to varied student’s perception of the program. This study aims to describe student’s perceptions of the implementation of the 2025 PLP II program from cognitive, affective, and conative aspects, as well as to identify the factors influencing these perceptions. This study employed a descriptive quantitative research design. Data were collected through a questionnaire administered to 72 students class of 2022, selected using simple random sampling. Data analysis was conducted using descriptive statistical analysis and Exploratory Factor Analysis (EFA). The findings indicate that student’s perceptions of PLP II within a positive category, as viewed from the cognitive aspect, obtained a mean score of 13,89, the affective aspect 14,14, and the conative aspect of 9,99. Factor analysis revealed three main factors influencing students’ perceptions: environmental support and learning motivation, academic guidance and preparation, and experience and self-reflection. These results highlight the importance of institutional support and reflective practice to enhance the effectiveness of PLP II in preparing professional Arabic language teachers.